2017
DOI: 10.1002/adma.201605529
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Nano–Bio Interfaces for Functional Biointegrated Devices

Abstract: A large amount of evidence has demonstrated the revolutionary role of nanosystems in the screening and shielding of biological systems. The explosive development of interfacing bioentities with programmable nanomaterials has conveyed the intriguing concept of nano-bio interfaces. Here, recent advances in functional biointegrated devices through the precise programming of nano-bio interactions are outlined, especially with regard to the rational assembly of constituent nanomaterials on multiple dimension scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 185 publications
0
76
0
Order By: Relevance
“…Drug resistance, referring to the failure of drug effectiveness for the cancer patients receiving chemotherapeutics, becomes an undesired obstacle for successful chemotherapy . Many clinical trials have reported the drug resistance of malignant with treatments of most popular chemotherapy drugs such as paclitaxel (PTX), doxorubicin (DOX), 5‐fluorouracil, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance, referring to the failure of drug effectiveness for the cancer patients receiving chemotherapeutics, becomes an undesired obstacle for successful chemotherapy . Many clinical trials have reported the drug resistance of malignant with treatments of most popular chemotherapy drugs such as paclitaxel (PTX), doxorubicin (DOX), 5‐fluorouracil, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Stretchable conductors are the basic building blocks of advanced flexible electronic devices, such as flexible display, skin‐like sensors, stretchable batteries, soft actuators and so forth . They are used in a vast number of soft and stretchable devices developed in recent years, including biointerfacing electrodes, transistors, mechanical sensors, energy devices and many more . To meet most application requirements, stretchable conductors need to remain conductive under tensile strain of more than 100%, and even more importantly, to show stable performance in terms of interfacial adhesion between conductive metal film and the supporting polymer substrate .…”
mentioning
confidence: 99%
“…Furthermore, nanoprobes may offer an exciting opportunity for imaging microrobots inside MRI. Such multimodal imaging probes could be utilized to obtain high‐resolution images of tissue in a highly localized region for precise operations …”
Section: Future Outlook and Conclusionmentioning
confidence: 99%
“…Such multimodal imaging probes could be utilized to obtain high-resolution images of tissue in a highly localized region for precise operations. [89,91]…”
Section: System-level Architecturementioning
confidence: 99%